2020
DOI: 10.1002/mrm.28159
|View full text |Cite
|
Sign up to set email alerts
|

Improved MR fingerprinting for relaxation measurement in the presence of semisolid magnetization transfer

Abstract: Purpose: To characterize and minimize the magnetization transfer (MT) effect in MR fingerprinting (MRF) relaxation measurements with a 2-pool (2P) MT model of multiple tissue types. Theory and Methods: Semisolid MT effect in MRF was modeled using 2P Bloch-McConnell equations. The combinations of MT parameters of multiple tissues (white [WM] and gray matter [GM]) were used to build the MRF dictionary. Both 1-pool (1P) and 2P models were simulated to characterize the dependence on MT. Relaxations measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…Additionally, the T 2 values were lower for the MRF techniques in the white and gray matter, which could be due to B 1 inhomogeneity or diffusion effects. However, the MRF T 2 values in this study are similar to T 2 values reported in other MRF studies of the brain 1,7,37–39 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, the T 2 values were lower for the MRF techniques in the white and gray matter, which could be due to B 1 inhomogeneity or diffusion effects. However, the MRF T 2 values in this study are similar to T 2 values reported in other MRF studies of the brain 1,7,37–39 …”
Section: Discussionsupporting
confidence: 90%
“…However, the MRF T 2 values in this study are similar to T 2 values reported in other MRF studies of the brain. 1,7,[37][38][39] The relaxation maps obtained using the multi-axis 2D spiral trajectory are similar to those obtained in other studies. Although they compare well with our proposed trajectory, there are small differences in image quality in which the Seiffert trajectory shows improved performance.…”
Section: F I G U R Esupporting
confidence: 84%
“…This process is expected to be relatively straightforward via the use of the open-source pulseq standard format sequences 31 . Similarly, the same model could be used to generate traditional water pool T and T signal dictionaries for conventional MRF 48 while taking into consideration the magnetization transfer effect on the measured relaxivity 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…The challenges associated with MRF are similar to those for any quantitative MRI technique: motion, spatial resolution, and B 0 and B 1 field non-uniformity. MRF may also be sensitive to magnetization transfer, partial volume, and slice profile effects 21,[28][29][30][31][32] . Spiral sampling use in MRF is advantageous in that it may reduce motion sensitivity by oversampling the centre of k-space 33 and matching a temporal pattern with MRF reconstruction.…”
mentioning
confidence: 99%